The relationship between perceived social support with anxiety, depression, and insomnia among Chinese college students during the COVID-19 pandemic: The mediating role of self-control - Zhao, Guojun; Xie, Fusen; Li, Shuangchen; Ding, Yuee; Li, Xu; Liu, Haijian (Frontiers in Psychiatry, 2022)
Object We aimed to investigate the associations between perceived social support and anxiety, depression, and sleep disturbance via self-control among Chinese college students during the COVID-19 pandemic. Materials and methods The Perceived Social Support Scale, Self-control Scale, Self-rating Anxiety Scale, Self-rating Depression Scale, and Insomnia Severity Index Scale were used to survey 1,997 college students during the COVID-19 pandemic, who submitted valid questionnaires (Mage = 19.93, SDage = 1.47, Range = 18–24 years, 62% female). Results The perceived social support and self-control were significantly positively correlated, and they were significantly and negatively associated with anxiety, depression, and insomnia. Further analysis found that self-control partially mediated the relationships between perceived social support with anxiety, depression, and insomnia. Conclusion During the COVID-19 pandemic, Chinese college students’ self-control played a partial mediating effect in the relationships between perceived social support and anxiety, depression, and insomnia. This study provides new insights and inspiration for improving college students’ mental health in the context of the pandemic.